OLED-on-silicon (OLEDoS) microdisplays: Technology challenges, design considerations, and adaptation in eXtended Reality (XR) ecosystem – Review - Rifat Kaçar; Ramis Berkay Seri̇n; Esin Uçar; Murat Artuç; Alper Ülkü; Barış Kınacı (Next Nanotechnology)
Microdisplay technologies include a variety of miniature display solutions designed to specific requirements in various applications, such as near-to-eye (NTE) platforms. Among these solutions, OLED based microdisplays stands out as an advanced micro-display technology that goes beyond the core principles of conventional OLED technology. This review investigates deeply into the landscape of OLED-on-Silicon (OLEDoS) microdisplays, providing a meticulous analysis of both the CMOS backplane and the OLED frontplane technology, along with subsidiary technologies. It thoroughly examines the challenges and potential drawbacks associated with each technology, offering a comprehensive understanding of their limitations. It also sheds light on the advancements and breakthroughs in the field and highlights the design considerations to overcome the outlined limitations. OLEDs are ideal for microdisplays due to their high contrast ratios, deep blacks, and fast response times, all essential for eXtended Reality (XR) experiences. Their self-emissive nature, which eliminates the need for backlighting, enabling thin, light, power-efficient displays with vibrant colors. These features make OLEDoS microdisplays particularly well-suited for NTE platforms. The review also examines the commercial landscape of OLEDoS, covering market trends, major industry players, and the adoption of these technologies across the industry. In conclusion, it provides a forward-looking perspective on the future of OLEDoS microdisplays, outlining emerging trends and opportunities within the rapidly evolving XR ecosystem.